2020
DOI: 10.1515/chem-2020-0121
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol content and antioxidant activities of Prunus padus L. and Prunus serotina L. leaves: Electrochemical and spectrophotometric approach and their antimicrobial properties

Abstract: The aim of the study was to compare the content of selected phytochemicals as well as the antioxidant and antimicrobial potential of the leaves of Prunus padus L. and Prunus serotina L., as there is very little research on this subject in the literature. Therefore, it is used to deepen knowledge on this subject. In addition, an electrochemical test was also carried out, which was not yet available for the above plants. Antibacterial studies have also been deepened to include the analysis of new strains of bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…There is still a lack of information on the influence of process methods on phenolics extraction from different plant parts of P. serotina. In previous studies (Olszewska 2005a(Olszewska , b, 2007Techlichowska et al 2020), phenolics compounds in Prunus serotina have also been reported, but, in our study, we performed a detailed analysis and accurate identification of a broad spectrum of phenolics in three different extracts.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…There is still a lack of information on the influence of process methods on phenolics extraction from different plant parts of P. serotina. In previous studies (Olszewska 2005a(Olszewska , b, 2007Techlichowska et al 2020), phenolics compounds in Prunus serotina have also been reported, but, in our study, we performed a detailed analysis and accurate identification of a broad spectrum of phenolics in three different extracts.…”
Section: Discussionmentioning
confidence: 85%
“…The main sources of polyphenolics in the European diet are beverages: tea and coffee (Clifford 1999;Scalbert and Williamson 2000;Zamora-Ros et al 2015). The leaves, flowers and bark of black cherry contain bioactive substances (Olszewska 2005a(Olszewska , b, 2007Techlichowska et al 2020). Extracts of these plant parts are used in traditional Mexican medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research material consisted of leaves, bark, and fruits of P. padus that had been selected in previous studies as a raw material with a higher antioxidant potential [6] of leaves comparing with P. serrotina. [6] All anatomical parts of the P. padus were in the orchard farm in Ozierany Małe in Podlasie, Poland (53º 13ʹ 14.865" N 23º 51ʹ 9.327" E). The leaves, bark, and fruits were lyophilized (CHRIST 1-4 LSC freeze dryer -Martin Christ Gefriertrocknungsanlagen GmbH, Osterode am Harz, Germany).…”
Section: Materials and Extract Preparationmentioning
confidence: 99%
“…We can also find organic acids such as citric acid, shikimic acid, malic acid, or quinic acid in its composition. Data on antioxidant properties of individual plant parts are available in the literature, [3][4][5][6] but they are not complete.…”
Section: Introductionmentioning
confidence: 99%